Typological study of traditional mosque ornamentation in Malaysia: comparison between traditional and modern mosque - Mohd Sojak, Siti Dalila; Utaberta, Nangkula (Department of Architecture, Faculty of Design and Architecture, Universiti Putra Malaysia, 2013)
Ornament is part of the essence of the building, growing together with the architecture and being an embellishment on the building to complement the architectural design. The Malays have built mosques with a distinctive pattern to describe the concept of divinity and naturalism moreover ensemble with the tropical climate. As a result, Malay traditional ornament comprise with understanding that clearly define the identity of its region. It symbolizes that the spread of Islamic Malay culture was manifested in the works of art of the Malays. However, development of modern mosque nowadays is well-liked of Middle East style which has given a new ‘meaning’ to the Islamic architecture in Malaysia. As a result, Malaysian Islamic architecture lost its identity through the diversity on the use of domes, maqsura, muqarnas and other syntax composition. The main purpose of this paper is to analyze the typology and classification of ornaments in Malaysia’s traditional mosque as a channel to the community towards understanding of the identity and also the framework of design thinking in ornaments particularly to the mosques in Malaysia. The report comprises the analysis of the typology and classification of ideas, theories and philosophies of Malay Traditional Ornaments focuses on the elements of mosque architecture as well comparison between traditional and modern mosque. It discusses the development and history of ornament in the Malay Traditional, concepts and philosophy that contains the idea and approach of its used in adaption of Islamic thoughts to the Malay world. Thus, it aims to initiate a comprehensive and thorough review of Malay ornamentation to the development of modern ornamentation for the future.